Novel Insights Into the Role of Glycans in the Pathophysiology of Glomerular Endotheliosis in Preeclampsia - Galvis-Ramírez, M. F.; Quintana-Castillo, J. C.; Bueno-Sanchez, J. C. (Frontiers in Physiology, 2018)
The polysaccharide heparan sulphate is ubiquitously expressed as a proteoglycan in extracellular matrices and on cell surfaces. In the glomerular filtration barrier, the action of the heparan sulphate is directly related to the function of glomerular filtration, mostly attributed to the sulphated domains that occur along the polysaccharide chain, as evidenced by fact that release of fragments of HS by heparanase significantly increase the permeability of albumin passage through the glomerular endothelium, Event that originates proteinuria. This review aims to show the importance of the structural domains of heparan sulphate in the process of selective permeability and to demonstrate how these domains may be altered during the glomerular inflammation processes that occur in preeclampsia.